Assessment of Scale Effects in the Experimental Evaluation of the Coefficient of Friction of Sliding Isolators. Issue 1 (2nd January 2022) - Quaglini, Virginio; Dubini, Paolo; Furinghetti, Marco; Pavese, Alberto
ABSTRACT: Sliding bearings have been extensively used to implement base isolation design in civil engineering works. Testing of isolators is conducted for characterizing the design properties to be used in structural analysis, as well as for verifying the performance of the devices before their application. The quantification of the effects of scaling specimens and testing on the observed coefficient of friction is an issue, due to the nonlinear dependence of friction on several factors like load, velocity and temperature. An effort to quantify such effects is pursued in the study. The coefficient of friction is parameterized as a function of few dimensionless quantities related to heating of the sliding surfaces, and similarity conditions are assessed under which the influence of scaling is below normal production variability.